Implementasi Pengelolaan Education Management Information System (EMIS) di Madrasah Diniyah Takmiliyah Al Hidayah Mojokerto - Dewi Nur Annisa Aliyan; Abdulloh Hamid (Jurnal Ilmiah Iqra', 2021)
Implementation Of Education Management Information System (EMIS) Management in Madrasah Diniyah Takmiliyah Al Hidayah Mojokerto. The Education Management Information System (EMIS) at Madrasah Diniyah Takmiliyah Al Hidayah is an information system that collects madrasa data online with one door. However, in reality, there are still obstacles and problems, such as the EMIS network, which is often problematic, and the information for updating EMIS data often seems sudden. This hinders the management of EMIS data at Madrasah Diniyah Takmiliyah Al Hidayah.This study aims to determine the effectiveness of EMIS in Madrasah Diniyah Takmiliyah Al Hidayah and its influence in the decision-making of the Mojokerto district government to determine Regional Operational Assistance for Madrasa Diniyah Takmiliyah Al Hidayah. This research has the benefit of letting the public know that at Madrasah Diniyah Takmiliyah Al Hidayah Mojokerto, in managing madrasa data, they have used an online system, namely EMIS, so that the data in EMIS Madrasah Diniyah Takmiliyah Al Hidayah can be reached anywhere and anytime. This study uses a qualitative descriptive method, while for data collection using interview, documentation, and observation techniques